Local Community Perception Towards Foreign Culture In Gili Trawangan - Suesilowati Suesilowati; Andi Ilham Satria Herlangga (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2026)
This study aims to find out how local people perceive foreign cultures in the tourist area of Gili Trawangan in Gili Indah Village, Pemenang District, North Lombok Regency (KLU). This type of research is qualitative research. The type of data used is primary data, which was obtained by conducting interviews with 15 respondents. The results of this study indicate that Gili Trawangan is famous for its beautiful beaches, so it is not surprising that many foreign tourists visit Gili Trawangan. The entry of foreign cultures into Gili Trawangan certainly brings cultural changes, but not all cultural changes have a negative impact, some also have a positive impact. The positive impacts of the entry of foreign cultures into Gili Trawangan include the existence of economic opportunities for some local people, the presence of foreign tourists brings great economic opportunities. The tourism industry provides employment and a source of income for the local population through accommodation, restaurants, transportation and various tourism-related businesses. Meanwhile, the negative impacts of the entry of foreign cultures into Gili Trawangan include foreign tourists who can bring cultural influences from their countries of origin.